ANALISIS YURIDIS PENJATUHAN HUKUMAN DI BAWAH ANCAMAN MINIMAL KEPADA PELAKU TINDAK PIDANA NARKOTIKA - Agusman Gulo (Jurnal Panah Hukum, 2025)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semi-synthetic. These drugs have the potential to reduce or change consciousness, eliminate the sense of taste, relieve or eliminate pain, and can cause depencence. Narcotics abuse can increase crime rates and also increase poverty. Based on this background, researchers are interested in examining the criminal juridical analysis of minimum threats against perpetrators of narcotics crimes (study decision number 724/Pid.Sus/2016/PN.Sky). The aim of the research is to determine and analyze criminal sentences with minimal threats to perpetrators of narcotics crimes (Decision Study 724/Pid.Sus/2016/PN.Sky). The type of research used is normative legal research. Normative legal research is legal research that examines literature studies, using a statutory regulation approach, case approach and analytical approach. The data collection technique used is secondary data obtained through primary, secondary and tertiary legal materials. The data analysis used is qualitative analysis and conclusions are drawn using a deductive method. Based on research findings and discussion, it can be concluded that imposing a sentence below the minimum threat for perpetrators of narcotics crimes (study decision number 724/Pid.Sus/2016/PN.Sky) is unfair, where the judge sentenced him to 1 year in prison. The punishment imposed on the perpetrator is very inappropriate where in article 112 paragraph (1) of law number 35 of 2009 concerning narcotics it is stated that anyone without the right to own, store, control or provide class 1 narcotics will be punished with imprisonment. imprisonment for a minimum of 4 (four) years, a maximum of 12 (twelve) years. The author suggests that the panel of judges stick to the applicable legal provisions, so that it can provide a deterrent effect for the perpetrators themselves.